Civil Engineering Students’ Perception on the Use of Mathematics in the Job - Pokharel, Thakur Prasad (KIC International Journal of Social Science and Management, 2024)
Use of Mathematics is common in civil Engineering job. The use of mathematics in civil engineering are influenced by different factors like attitude of learners and teachers, learning environment, and realization of mathematics as a part of the job. It is the need to identify how Civil Engineering students feel importance of mathematics in the job. Thus, the objective of the study was to investigate the perception of Civil Engineering students on the use of mathematics in Civil Engineering job taking into consideration of realization of mathematics, mathematical background and engineering as a career, attitude of students and teacher, and learning environment as input (independent). The sample for the study consists of 228 students of civil engineering purposefully selected from the colleges in Pokhara valley. A six –point Likert –scale survey instrument having 29 structured questions was used and administered. The result of the study was obtained by analyzing the data through descriptive tools of statistics, CV, correlation, and regression analysis. Descriptive, ANOVA, CV and correlation revealed that most of the students were strongly agree with the statement that mathematics is the foundation of engineering. It also found that the use of mathematics in civil engineering job is significantly correlated with attitude of learners and teachers, learning condition, realization of mathematics, and background of mathematics and engineers as a career. Though the study was focused on the students of civil engineering at Pokhara valley, such study should be expanded in other places to validate and generalize these results.